Uji Efektivitas Kombinasi Filter-Adsorpsi Arang Tempurung Kelapa Pada Penurunan COD dan TSS Limbah Cair RPH - Navisa Ika Irmayanti; Mohamad Mirwan (Jurnal Serambi Engineering, 2025)
Slaughterhouse waste is one of the sources of water pollution. If not properly managed, the slaughterhouse industry can have a significant negative impact on the environment and humans. The purpose of this study was to analyze the effectiveness of the combination of coconut shell charcoal filter-adsorption on the reduction of COD and TSS of slaughterhouse liquid waste. Slaughterhouse liquid waste is flowed into a filtration-adsorption reactor with a flow rate of 54 ml/minute and using the Slow Sand Filter (SSF) method, downflow flow with a continuous system. There are five reactors namely filtration-adsorption reactors A, B, C, D and E with different filter media in each reactor with sampling times of 0, 30, 60, 90 and 120 minutes. The variables measured were the effectiveness of the filter media reactor in reducing COD and TSS parameters, the adsorption capacity of reactors B and C, and the breakthrough time on the filter media of reactors B and C. The results showed that the best reactor effectiveness was in reactor E, which was able to remove 75% COD and 70.8% TSS parameters with a mesh size of 100 and a sampling time of 120 minutes. The highest adsorption capacity on 10 mesh and 100 mesh coconut shell activated carbon media was 0.0222 mg/mg adsorbent and 0.0233 mg/mg adsorbent, respectively. The breakthrough time obtained varied from 0.78 days to 1.60 days in each reactor.